2019
DOI: 10.1016/j.jaad.2018.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to limit systemic antibiotic use in acne: Systemic alternatives, emerging topical therapies, dietary modification, and laser and light-based treatments

Abstract: Acne is one of the most common diseases worldwide and affects approximately 50 million individuals in the United States. Oral antibiotics are the most common systemic agent prescribed for the treatment of acne. However, their use may be associated with a variety of adverse outcomes including bacterial resistance and disruption of the microbiome. As a result, multiple treatment guidelines call for limiting the use of oral antibiotics in the treatment of acne, although actual prescribing often does not follow th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 87 publications
(111 citation statements)
references
References 175 publications
(161 reference statements)
2
102
0
7
Order By: Relevance
“…Oral contraceptives containing estrogen and spironolactone are regarded as second-line treatment choices in females with inflammatory acne (3,4). Moreover, it has been suggested that pulsed dye laser and 1,450 nm diode laser could be therapeutic alternatives (5).…”
Section: Introductionmentioning
confidence: 99%
“…Oral contraceptives containing estrogen and spironolactone are regarded as second-line treatment choices in females with inflammatory acne (3,4). Moreover, it has been suggested that pulsed dye laser and 1,450 nm diode laser could be therapeutic alternatives (5).…”
Section: Introductionmentioning
confidence: 99%
“…First, and most important, was in minimizing the development of antibiotic resistance, which is associated with disruption of the normal flora, bacterial resistance among other organisms, and increased rates of upper respiratory infection and pharyngitis. 16 Oral antibiotics are the most common systemic agent prescribed for the treatment of acne. However, antibiotic resistance is a growing problem across medicine and rates of antibiotic resistance among isolates of P. acnes have been rising, including to tetracycline-class antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…This timeline to improvement was not surprising because previous literature has supported the notion that hormonal therapies can take several months to effect a clinical improvement. 12,13 Our data suggest that it is important to counsel patients about the expected timeline to efficacy so they do not discontinue spironolactone treatment prematurely.…”
Section: Adverse Effectsmentioning
confidence: 92%